Design and analysis of eco-efficient stoves in latinamerica: a systematic review of environmental and social impact - Jaimes Silva, Catherine Johana; Tovar Quintero, Jennifer; Arboleda Puerta, Jorge Enrique; Gutierrez Perdomo, Edwin Santiago (Ingeniería Solidaria, 2026)
Introduction: This review article is the result of research conducted at the Universidad Nacional Abierta y a Distancia (UNAD) in 2024. It analyzes databases and organizations involved in the production of eco-efficient stoves, identifying health aspects, design features, and the use of biofuels between 2017 and 2024 in Latin America.Problem: Traditional wood stoves remain prevalent in rural areas of Latin America, posing serious health and environmental risks due to inefficient combustion and high pollutant emissions.Objective: The objective is to identify diseases and environmental and social impacts associated with traditional stoves, and to analyze the most relevant eco-efficient stove recommendations for rural communities in Latin America.Methodology: A systematic literature review was conducted following PRISMA guidelines, including scientific articles and bibliometric analysis. The topics addressed include combustion systems, particulate matter emissions, biofuel gas production, respiratory illnesses, and improvements in combustion chambers for better eco-efficiency.Results: The review highlights stove models such as Huellas, FN, Lorena, and Patsari, which improve energy use and reduce emissions. The study shows that Norway, the United States, and Chile lead research in this field. However, only 14 of 116 Latin American authors have published more than one article, revealing a gap in consistent regional research. Trends by country and topic were also identified.Conclusion: Bibliometric analysis is essential to understanding the impact of biomass combustion on health and the environment, and to guide future research efforts.Originality: This review presents a comparative view of stove models, health consequences of biomass use, and design features of eco-efficient technologies in Latin America.Limitations: Databases provide information on health and general use, but offer limited detail on specific eco-efficient stove models, resulting in fragmented information.
Keywords: Biomass; eco-efficiency; emissions; wood stoves